THE ROLE OF RATIONAL NUTRITION IN CARIES PREVENTION (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article explores the critical role of sugar consumption in the development of dental caries, emphasizing the interaction between cariogenic bacteria, particularly Streptococcus mutans, and dietary fermentable carbohydrates like sucrose. It highlights that frequent intake of simple sugars contributes to enamel demineralization by lowering the oral pH below the critical level of 5.5. The article also outlines dietary strategies for expecting mothers, underlining the importance of proper nutrition and oral hygiene during pregnancy. It stresses that poor maternal nutrition can lead to enamel hypoplasia in infants, significantly increasing their risk for early childhood caries. Consequently, health professionals should educate pregnant women on healthy eating, limiting sugar intake, and adhering to vitamin and mineral guidelines to promote long-term oral health in children.